Implementation of Work Immersion in the New Normal: Basis for Students’ Quality Performance and Satisfaction - Cabile Jr, Democrito C (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This study evaluated the implementation of work immersion in the new normal, students' quality performance, and work immersion satisfaction. The relationship between variables and the mediating effect of students' quality performance between work immersion implementation and student satisfaction was also investigated. Adherence, exposure, quality of delivery in terms of work immersion curriculum, work immersion processes, and work immersion assessment, as well as participant responsiveness, were used to assess the extent of work immersion implementation. In addition, the level of satisfaction among students was evaluated using Task values (attainment value, intrinsic value, utility value, and cost); Motivation factors (work itself, achievement, and responsibility); and Hygiene factors (administrative policies, supervision, interpersonal, and working conditions). On the other hand, students’ quality performance was gauged base on teamwork, communication, attendance/punctuality, productivity/resilience, initiative/proactivity, judgement/decision-making, and dependability. Respondents are Grade 12 students from public secondary schools in the SDO Tayabas who have participated in actual work immersion activities in an authentic workplace. The structured questionnaire was created and validated to collect data from respondents via Google Forms to determine the extent of the research variables and their association. These data were analyzed to obtain reliable and valid study results. The study's findings revealed that work immersion program implementation is significantly related to student satisfaction. Work immersion program implementation is significant to student quality performance; student satisfaction creates a relationship with work immersion program implementation. The mediation analysis results indicate that the overall student’s quality performance can transmit the effect of influenced implementation of work immersion, which increases student Satisfaction. Also, partial mediation exists considering the extent of the mediating effect of students' quality performance between the work immersion implementation and the students' satisfaction with work immersion. This is due to the analysis that the work immersion implementation as the independent variable significantly affects a mediating variable, which is the students' quality performance. The students' quality performance as the mediating variable has a direct impact on the students' satisfaction with work immersion as the independent variable.